The Development of ECIRR Learning Model Containing Archipelago Local Wisdom on Mechanics Topic - Lutfiyanti Fitriah; Akhmad Firdaus; Dahlia Dahlia; Septiana Septiana (Jurnal Ilmiah Pendidikan Fisika, 2023)
This study aimed to develop an ECIRR (Elicit, Confront, Identify, Resolve, and Reinforce) learning model containing Indonesian local wisdom on mechanics in Fundamental Physics lectures. The type of research was Research and Development with the ADDIE model. The number of samples in this study was 28, chosen by purposive sampling. The instruments of this research were validation sheets, observation sheets, and response questionnaires. Data analysis used the Aiken formula and descriptive statistics. Based on the results of the study, it was known that the validity of the content of the learning model was 1.00 with a valid category; the average implementation of lecturer activities was 4.56 with a very good category; the average implementation of student activities was 4.36 with a very good category; and the student response to the model was good. This research concluded that the learning model developed was valid, can be implemented in lectures, and gets a good response from students. Thus, the learning model that has been developed can be used on the topic of mechanics in Fundamental Physics lectures.